Perancangan Mesin Pemipih dan Pemotong Adonan Mie Penambahan Kerangka Pada Output Conveyor - Thoriq Azis; Iman Dirja; Kardiman Kardiman (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the world of MSMEs (Micro, Small and Medium Enterprises) made from wheat flour, the most popular among the people of Indonesia. For the process of making noodles using the traditional method which will take a very long time. The design of this noodle flattening and cutting machine aims to analyze the needs of noodle producers and calculate the results obtained from the design of the noodle flatter and cutter with the addition of a framework. From the results of the calculation analysis that has been obtained: power generated = 0.75 kW, design power = 1.2 kW, correction factor = 1.6, torque moment = 834.8 kg.mm, pulley rotation 1400 rpm, 840 rpm, 710.7 rpm, diameter of large pulley = 50 mm, 65 mm, diameter of small pulley = 30 mm, 55 mm, linear speed = 0.7 m/s, 0.77 m/s, length of circumference of v-belt = 225.6 mm, 636.9 mm, axle distance = 28.6 mm, 224.1 mm, V-belt angle = 139.9°, 154.6°. And the size of the engine frame is 750 mm x 500 mm x 950 mm.